Modulation of γδ T Cell Activity by Bisphosphonates in Neoplasms Resistant to Conventional Immunotherapy: An Update - Meneses do Rêgo, Amália Cinthia; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2024)
Bisphosphonates (BPs) are traditionally used to manage bone diseases, but recent evidence suggests they may play a significant role in cancer immunotherapy by modulating γδ T cell activity. These agents, particularly nitrogen-containing bisphosphonates, activate Vγ9Vδ2 T cells, enhancing their cytotoxicity against tumor cells. However, gaps remain in understanding the differential effects of bisphosphonates on various γδ T cell subsets, optimal dosing regimens, and their impact on the broader tumor microenvironment. This review synthesizes knowledge on bisphosphonate-induced γδ T cell modulation, explores potential resistance mechanisms, and evaluates clinical applicability across different tumor types. It identifies biomarkers for patient stratification, considers synergistic effects with other therapies, and discusses the economic and practical implications of integrating bisphosphonates into standard oncology practice. Addressing these gaps is essential for optimizing bisphosphonates as immunomodulatory agents, advancing cancer immunotherapy strategies, and improving patient outcomes.